1980
DOI: 10.1017/s0014479700010802
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Ratio for Quantifying Competition Between Intercrops

Abstract: A simple competitive ratio (CR) is proposed as a measure of intercrop competition, to indicate the number of times by which one component crop is more competitive than the other. Intercropping data show that this CR term could be useful in (i) comparing the competitive ability of different crops, (ii) measuring competitive changes within a given combination, (iii) identifying which plant characters are associated with competitive ability, and (iv) determining what competitive balance between components is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
289
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(300 citation statements)
references
References 4 publications
(4 reference statements)
6
289
0
5
Order By: Relevance
“…The competitive ratio (CR) was used to evaluate which one crop competes with the other in an intercropping system (Willey & Rao 1980;Wahla et al 2009), and can be calculated by following the formula (Bhatti et al 2006):…”
Section: Competitive Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The competitive ratio (CR) was used to evaluate which one crop competes with the other in an intercropping system (Willey & Rao 1980;Wahla et al 2009), and can be calculated by following the formula (Bhatti et al 2006):…”
Section: Competitive Ratiomentioning
confidence: 99%
“…Safflower dominated and occupied a superior ecological niche in the intercropping system. The competitive ratio (CR) is considered a better measure of competitive ability of the crops compared with the RCC and aggressivity (Willey & Rao 1980;Wahla et al 2009). Higher bitter vetch CR values in our study indicated that in different intercropping patterns, safflower was more competitive than bitter vetch.…”
Section: Relative Crowding Coefficient (Rcc)mentioning
confidence: 99%
“…the yield that could be expected with no interaction, when a linear increase with mixture proportion is assumed (cf. Willey and Rao 1980;Jolliffe et al 1984; stippled lines in replacement series graphs of Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…It was determined according to Willey and Rao (1980) The statistical analysis for data was carried out according to Gomez and Gomez (1984). L.S.D test at 5% significant level was used to compare the differences between treatment means.…”
Section: -Competitive Ratio (Cr)mentioning
confidence: 99%